Lagos bat virus in Kenya - Kuzmin, Ivan V; Niezgoda, Michael; Franka, Richard; Agwanda, Bernard; Markotter, Wanda; Beagley, Janet C; Urazova, Olga Y; Breiman, Robert F; Rupprecht, Charles E (Journal of clinical microbiology, 2008)
During lyssavirus surveillance, 1,221 bats of at least 30 species were collected from 25 locations in Kenya. One isolate of Lagos bat virus (LBV) was obtained from a dead Eidolon helvum fruit bat. The virus was most similar phylogenetically to LBV isolates from Senegal (1985) and from France (imported from Togo or Egypt; 1999), sharing with these viruses 100% nucleoprotein identity and 99.8 to 100% glycoprotein identity. This genome conservancy across space and time suggests that LBV is well adapted to its natural host species and that populations of reservoir hosts in eastern and western Africa have sufficient interactions to share pathogens. High virus concentrations, in addition to being detected in the brain, were detected in the salivary glands and tongue and in an oral swab, suggesting that LBV is transmitted in the saliva. In other extraneural organs, the virus was generally associated with innervations and ganglia. The presence of infectious virus in the reproductive tract and in a vaginal swab implies an alternative opportunity for transmission. The isolate was pathogenic for laboratory mice by the intracerebral and intramuscular routes. Serologic screening demonstrated the presence of LBV-neutralizing antibodies in E. helvum and Rousettus aegyptiacus fruit bats. In different colonies the seroprevalence ranged from 40 to 67% and 29 to 46% for E. helvum and R. aegyptiacus, respectively. Nested reverse transcription-PCR did not reveal the presence of viral RNA in oral swabs of bats in the absence of brain infection. Several large bat roosts were identified in areas of dense human populations, raising public health concerns for the potential of lyssavirus infection.